Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

What wrong with this proof?

$(-1)=(-1)^{\frac{2}{2}}=(-1)^{2\times \frac{1}{2}}=\sqrt{1}=1$ then $1=-1$

share|improve this question
    
The issue is how you define $x \mapsto (x)^{\frac{1}{2}}$. –  copper.hat Oct 31 '13 at 18:11

3 Answers 3

up vote 7 down vote accepted

$x^{\frac{1}{2}}$ is a multiple-valued "function", since in general $x$ has two square roots. One could also write:

$$\sqrt1=-1$$

share|improve this answer

enter image description here

it is fake suppose f(x)=x and g(x)=(x)^(2/2)

f(x) is not equal to g(x) domain of both is R but g(x)=|x| instead of f(x)=x

share|improve this answer
    
+1 for literally writing it down :D –  CODE Oct 31 '13 at 18:57

$(-1)^{2 \times\frac{1}{2}}$ is not equal to $\sqrt{1}$. The correct way to simplify $(-1)^{2 \times\frac{1}{2}}$, using universally accepted orders of operation (because they work), is to start by simplifying the exponent ${2 \times\frac{1}{2}}$ to $1$. Then you get $(-1)^1$ , which is equal to $-1$, which is where you started.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.